International Standards in the Area of Combating the Financing of Terrorism and Extremism - BAISAGATOVA, Diana Bekbolatovna; KASIMOVA, Madina Orynbaevna; SYZDYKOVA, Manara Uralchanovna; KEMELBEKOV, Saken Talipbaevich (Journal of Advanced Research in Law and Economics, 2017)
The paper deals with issues of defining international standards in the area of combating the financing of terrorism and extremism. Regulatory legal acts issued by the UN since its founding to the present day regarding combating the financing of terrorism and extremism, as well as corresponding acts of Council of Europe, CIS, others groups of states, Republic of Kazakhstan are studied. Legal acts adopted within the framework of the UN, the CIS, individual groups of states, the Republic of Kazakhstan on the fight against terrorism, separatism, and extremism are analyzed. A problem is identified that to the present day there’s no uniform definition of such main legal notions used in this area as ‘violence’, ‘extremism’, ‘war’ and ‘terrorism’, ‘terrorist organization’, ‘extremist organization’. Another problem related to the world practice of recognizing an organization as terrorist is revealed. Its two main mechanisms, political and judicial, are used in the world practice. The political mechanism involves active participation of corresponding government bodies. A court plays a key role in the recognizing an organization as terrorist in the judicial mechanism. Certainly, the judicial mechanism of recognizing organizations, groups as terrorist is preferred. In this case there are more guarantees of compliance with law, justice, impartiality, as well as reservation of personal fundamental rights and freedoms. The political mechanism of recognizing groups or organizations as terrorist suffers from the use of ‘double standards’. On the basis of the undertaken research the author states that the Republic of Kazakhstan should come forward with an initiative concerning development of a UN regulatory legal act on the unification of international standards in the area of combating the financing of terrorism and extremism.
Keywords: terrorism; extremism; antiterrorist activity; financing; terrorist organization; model legislation